Ethical reflections on the financial crisis 2007/2008 : making use of smith, musgrave and rajan - Ver Eecke, Wilfried (SpringerBriefs in Economics, 2013)
In this book the author reflects on the philosophical and ethical bases of the financial crisis 2007-08 and the subsequent recession. He finds in Adam Smith solid arguments for the new free market economy, capitalism, but also arguments for a  role for the government in the case of public goods (roads) and of merit goods (education, control of banking). Where the provision of public goods requires that the government respect consumer sovereignty there the provision of merit goods legitimizes the violation of that principle. By making use of the history of economic thought (e.g., the neo-liberal tradition) the author demonstrates that Musgrave's idea of merit goods can be expanded to eleven domains in which the government has an important function. He legitimizes that move by using the Kantian argument that we must accept the possibility conditions for what we want. The author demonstrates that Rajan, Reich and Reinhart & Rogoff make use of seven of his eleven categories of merit goods in order to explain the financial crisis 2007-08 and the subsequent recession. The author thereby provides a philosophical and ethical analysis of the government's failures at the basis of the financial crisis.